PRINSIP NETRALITAS PRESIDEN DALAM PELAKSANAAN PEMILIHAN UMUM YANG DEMOKRATIS - Selvia Fitri Maulida; Sholikul Hadi (Journal of Innovation Research and Knowledge, 2025)
Indonesia is a democratic country that makes elections a symbol of democracy. Elections serve as a means of electing aspirational, qualified, and responsible representatives of the people. Law No. 7/2017 regulates the political rights of all citizens, including the President and Vice President to campaign in elections, provided that they do not use state facilities and are on leave outside the state's responsibility. However, the President's position as a symbol of state leadership requires strict neutrality principles to keep democracy alive and avoid potential abuse of power. This study aims to analyze the President's involvement in elections based on Law No. 7/2017, assess whether the existing provisions already reflect the principle of neutrality, and formulate ideal arrangements to maintain a fair democracy. Using the normative juridical method, this study finds that although the President has the right to campaign, the existing rules still leave room for abuse of power and public distrust. Therefore, stricter restrictions on the use of state facilities and the President's status in the campaign are needed to ensure a truly neutral and democratic election